2022
DOI: 10.1155/2022/9151294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Intensity, and Risk Factors for Helminth Infections in Pigs in Menoua, Western Highlands of Cameroon, with Some Data on Protozoa

Abstract: Helminthes affect satisfactory pig farming by causing poor growth rate and infertility. The objective of this study was to investigate the occurrence of helminthes in pig production, as well as factors influencing their prevalence in Menoua, Western Highlands of Cameroon. Thus, 597 fecal samples from 100 farms of three production types (farrower, grower, and farrow-to-finish) were collected together with data on farmer and management characteristics. Samples were qualitatively and quantitatively analyzed. Eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The Sardinian studies showed the smallest differences in incidence; the difference was only −0.75% (Tables 4-6). Cameroon pig farm 0.2% 2022 [35] Italy (Sardinia) woodland area wild boar 13.6% 2022 [45] Brazil woodland area wild boar 1.04% 2023 [38] Research data on M. hirudinaceus from different parts of the world. Occurrence of A. suum and M. hirudinaceus by country, differences compared to Hungarian data.…”
Section: Discussionmentioning
confidence: 99%
“…The Sardinian studies showed the smallest differences in incidence; the difference was only −0.75% (Tables 4-6). Cameroon pig farm 0.2% 2022 [35] Italy (Sardinia) woodland area wild boar 13.6% 2022 [45] Brazil woodland area wild boar 1.04% 2023 [38] Research data on M. hirudinaceus from different parts of the world. Occurrence of A. suum and M. hirudinaceus by country, differences compared to Hungarian data.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of these zoonotic parasites may get complex if not curbed as, for instance, an aberrant A. suum infection has been reported in a dog in China [ 39 ] underpinning the domestic animal as a potential host alongside rodent reservoirs [ 13 ]. The other identified parasites, which have also been identified within Ghana and outside by other researchers, are equally important as they cause significant losses in pigs [ 16 , 28 , 40 ] although farmers may be unaware due to subclinical infections [ 40 ]. The impact of polyparasitism on the affected pigs was not examined in the present study, but it is thought to be significant due to the higher rate polyparasitism seen.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal parasites, i.e., helminths and protozoans, tend to hinder profitable pig production; causing poor feed conversion [10], delayed estrus, and conception rate [13], producing lesions that may lead to condemnation of organs and or carcasses [14] and even death [15]. Also, pigs are host to a number of zoonotic parasites that have an impact on public health [16][17][18]. Meanwhile, the epidemiology of intestinal infections in pigs is not well understood in many localities, but this is essential if good disease management strategies are to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Hyostrongylus rubidus, Strongyloides ransomi, Trichostrongylus sp., Ascaris suum, Metastrongylus sp., Oesophagostomum dentatum, Trichuris suis and Macracanthorhynchus hirudinaceus (Nansen & Roepstorff, 1999;Kouam & Ngueguim, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pigs could carry many gastrointestinal parasites (GIPs) which would hinder growth of pigs, leading to significant economic loss to the livestock industries (Joachim et al., 2001 ). Some commonly encountered intestinal helminth parasites in pigs include Hyostrongylus rubidus , Strongyloides ransomi , Trichostrongylus sp., Ascaris suum , Metastrongylus sp., Oesophagostomum dentatum , Trichuris suis and Macracanthorhynchus hirudinaceus (Nansen & Roepstorff, 1999 ; Kouam & Ngueguim, 2022 ).…”
Section: Introductionmentioning
confidence: 99%